Evaluation of the 3M™ Molecular Detection Assay (MDA) 2 – Salmonella for the Detection of Salmonella spp. in Select Foods and Environmental Surfaces: Collaborative Study, First Action 2016.01. (27th November 2019) - Bird, Patrick; Flannery, Jonathan; Crowley, Erin; Agin, James R; Goins, David; Monteroso, Lisa; ,
Abstract: The 3M™ Molecular Detection Assay (MDA) 2 – Salmonella uses real-time isothermal technology for the rapid and accurate detection of Salmonella spp. from enriched select food, feed, and food-process environmental samples. The 3M MDA 2 – Salmonella was evaluated in a multilaboratory collaborative study using an unpaired study design. The 3M MDA 2 – Salmonella was compared to the U.S. Food and Drug Administration Bacteriological Analytical Manual Chapter 5 reference method for the detection of Salmonella in creamy peanut butter, and to the U.S. Department of Agriculture, Food Safety and Inspection Service Microbiology Laboratory Guidebook Chapter 4.08 reference method "Isolation and Identification of Salmonella from Meat, Poultry, Pasteurized Egg and Catfish Products and Carcass and Environmental Samples" for the detection of Salmonella in raw ground beef (73% lean). Technicians from 16 laboratories located within the continental United States participated. Each matrix was evaluated at three levels of contamination: an uninoculated control level (0 CFU/test portion), a low inoculum level (0.2–2 CFU/test portion), and a high inoculum level (2–5 CFU/test portion). Statistical analysis was conducted according to the probability of detection (POD) statistical model. Results obtained for the low inoculum level test portions produced difference in collaborator POD values of 0.03 (95% confidence interval, −0.10 to 0.16) for raw ground beef and 0.06 (95% confidence interval, −0.06 to 0.18) for creamy peanut butter, indicating no statistically significant difference between the candidate and reference methods.